Endgame? The Fiscal Crisis of the German State - Wolfgang Streeck (Max Planck Institute for the Study of Societies, 2007)
A longer-term perspective reveals the historical exhaustion of the financial resources of the democratic interventionist state of the postwar period. German politics present and future is shaped by a deep crisis of public finance. Its current expression is an apparently insurmountable conflict between four equally urgent political objectives: paying for social security by general taxes, rather than payroll taxes, to lower labor costs; consolidating public budgets and reducing the public debt; cutting taxes on mobile capital; and increasing public investment in response to new social problems and changing economic conditions. Analysis of the fiscal problems of the German state casts new light on the turbulences of German politics since the Schröder government's first term. – – In längerfristiger Perspektive zeigt sich ein säkularer Prozess der Erschöpfung der finanziellen Ressourcen des demokratischen Interventionsstaats der Nachkriegsphase. Die gegenwärtige und zukünftige deutsche Politik steht im Zeichen einer tiefen Krise der Staatsfinanzen. Deren aktueller Ausdruck ist ein anscheinend unüberwindlicher Konflikt zwischen vier gleichermaßen unabweisbaren politischen Zielen: der Verlagerung der Finanzierung der Sozialversicherung auf Steuern zum Zweck einer nachhaltigen Senkung der Arbeitskosten; der Konsolidierung der öffentlichen Finanzen durch Abbau der Haushaltsdefizite und der Schuldenlast; einer Senkung der Besteuerung der Erträge mobilen Kapitals; sowie verstärkter öffentlicher Investitionen in Antwort auf neuartige gesellschaftliche Probleme und wirtschaftliche Konkurrenzbedingungen. Die Analyse der Finanzierungsprobleme des deutschen Staates wirft ein neues Licht auf die Turbulenzen der deutschen Politik seit der ersten Amtsperiode der Regierung Schröder.
Keywords: 300; Finanzpolitik; Haushaltskonsolidierung; Sozialstaat; Standortpolitik; Deutschland